Limites probatórios da delação premiada frente à verdade no processo penal - Mandarino, Renan Posella [UNESP] (2016)
The evidence in the criminal procedure is produceded by analog reconstruction of facts bt the parties and collaborators of justice, through the perception and individual interpretation about particular reality. The truth is linked to the production procedure evidence, so that the criminal prosecution is oriented by the “need” to reach the truth. However, this search for truth collides with the constitucional, legal and linguistic limits. The plea bargaining are collaborative investigative techniques used to unveil the crimes of high complexity. Its ai mis to promote the participarion of the accused in the search for truth. The main objective of this research is to analyse the evidentiary limits os plea bargaining front to the formartion of truth in criminal procedure. To examine the problem proposed, in the first chapter, the criminal procedure is contextualized in the contemporary society, filled with risk and State efficiency. In the second chapter, find out system proof anda the formation os truth in criminal procedure. Then, the investigantion focuses on the legal nature and the rules concerning the plea bargaining, including negotiation model and american influences in the brazilian cirminal procedure system. Finally, it examines the limits to the use of the premial agreements are submittes in the lawsuit. The procedural methology is the bibliographical anda the method of approach is the hypothetical-deductive. One hypothesis suggests that, from the use of plea bargaining, agreements have been established a new truth procedure, negoating character. To assume the plea bargaining institute in the contexto of posmodern society, the conclusion of reach is that the negoating model guides the search for truth in the process, but not only that. The purpose of pacts premials goes beyond the pursuit of truth, because it aims to also manage the risk in social systems.